Bortezomib with lenalidomide and dexamethasone versus lenalidomide and dexamethasone alone in patients with newly diagnosed myeloma without intent for immediate autologous stem-cell transplant (SWOG S0777): a randomised, open-label, phase 3 trial. Issue 10068 (4th February 2017) - Durie, Brian G M; Hoering, Antje; Abidi, Muneer H; Rajkumar, S Vincent; Epstein, Joshua; Kahanic, Stephen P; Thakuri, Mohan; Reu, Frederic; Reynolds, Christopher M; Sexton, Rachael; Orlowski, Robert Z; Barlogie, Bart; et al.
Summary: Background: Lenalidomide plus dexamethasone is a reference treatment for patients with newly diagnosed myeloma. The combination of the proteasome inhibitor bortezomib with lenalidomide and dexamethasone has shown significant efficacy in the setting of newly diagnosed myeloma. We aimed to study whether the addition of bortezomib to lenalidomide and dexamethasone would improve progression-free survival and provide better response rates in patients with previously untreated multiple myeloma who were not planned for immediate autologous stem-cell transplant. Methods: In this randomised, open-label, phase 3 trial, we recruited patients with newly diagnosed multiple myeloma aged 18 years and older from participating Southwest Oncology Group (SWOG) and National Clinical Trial Network (NCTN) institutions (both inpatient and outpatient settings). Key inclusion criteria were presence of CRAB (C=calcium elevation; R=renal impairment; A=anaemia; B=bone involvement) criteria with measurable disease (measured by assessment of free light chains), Eastern Cooperative Oncology Group (ECOG) performance status of 0–3, haemoglobin concentration 9 g/dL or higher, absolute neutrophil count 1 × 10 3 cells per mm 3 or higher, and a platelet count of 80 000/mm 3 or higher. We randomly assigned (1:1) patients to receive either an initial treatment of bortezomib with lenalidomide and dexamethasone (VRd group) or lenalidomide and dexamethasone alone (Rd group). Randomisation was stratified based on International Staging System stage (I, II, or III) and intent to transplant (yes vs no). The VRd regimen was given as eight 21-day cycles. Bortezomib was given at 1·3 mg/m 2 intravenously on days 1, 4, 8, and 11, combined with oral lenalidomide 25 mg daily on days 1–14 plus oral dexamethasone 20 mg daily on days 1, 2, 4, 5, 8, 9, 11, and 12. The Rd regimen was given as six 28-day cycles. The standard Rd regimen consisted of 25 mg oral lenalidomide once a day for days 1–21 plus 40 mg oral dexamethasone once a day on days 1, 8, 15, and 22. The primary endpoint was progression-free survival using a prespecified one-sided stratified log rank test at a significance level of 0·02. Analyses were intention to treat. This trial is registered withClinicalTrials.gov, numberNCT00644228 . Findings: Between April, 2008, and February, 2012, we randomly assigned 525 patients at 139 participating institutions (264 to VRd and 261 to Rd). In the randomly assigned patients, 21 patients in the VRd group and 31 in the Rd group were deemed ineligible based mainly on missing, insufficient, or early or late baseline laboratory data. Median progression-free survival was significantly improved in the VRd group (43 months vs 30 months in the Rd group; stratified hazard ratio [HR] 0·712, 96% CI 0·56–0·906; one-sided p value 0·0018). The median overall survival was also significantly improved in the VRd group (75 months vs 64 months in the Rd group, HR 0·709, 95% CI 0·524–0·959; two-sided p value 0·025). The rates of overall response (partial response or better) were 82% (176/216) in the VRd group and 72% (153/214) in the Rd group, and 16% (34/216) and 8% (18/214) of patients who were assessable for response in these respective groups had a complete response or better. Adverse events of grade 3 or higher were reported in 198 (82%) of 241 patients in the VRd group and 169 (75%) of 226 patients in the Rd group; 55 (23%) and 22 (10%) patients discontinued induction treatment because of adverse events, respectively. There were no treatment-related deaths in the Rd group, and two in the VRd group. Interpretation: In patients with newly diagnosed myeloma, the addition of bortezomib to lenalidomide and dexamethasone resulted in significantly improved progression-free and overall survival and had an acceptable risk-benefit profile. Funding: NIH, NCI, NCTN, Millennium Pharmaceuticals, Takeda Oncology Company, and Celgene Corporation.